Elevating Jack Beans Sauce: A Visual Identity Strategy for Enhanced Brand Recognition - Kusumawati, Yudhistya Ayu; Gunawan, Elizabeth Paskahlia; Lukiyanto, Kukuh; Yana, Erlyana (Institut Bisnis dan Teknologi Indonesia, 2024)
The MSMEs sector is able to contribute to economic growth in Indonesia. Jawa Sehati Mulia is an MSMEs which operates in the field of producing jack beans sauce namely Korochi made from local jackbeans or Phaseolus lunatus L. When researching a visual identity strategy for jack beans sauce with the goal of enhancing brand recognition, qualitative research methods are particularly useful in understanding the deeper perceptions, emotions, and cultural nuances associated with the brand. By using design thinking method, this research explores the critical role of visual identity in building brand recognition and fostering consumer engagement for a unique, plant-based product. Despite its healthy and sustainable attributes, Jack Beans Sauce has yet to fully establish a strong brand presence in a competitive food market. The study focuses on developing a cohesive and appealing visual identity that reflects the brand’s core values—health, sustainability, and innovation—while appealing to a target audience of health-conscious and environmentally-aware consumers. By creating a distinct logo, color scheme, typography, and packaging design, the research aims to enhance the brand's visibility and differentiate it from competitors. Additionally, the study examines how this visual identity can be applied consistently across digital platforms and physical touchpoints to create a unified brand experience. Ultimately, this research seeks to provide actionable insights on how a well-crafted visual identity can elevate brand awareness, strengthen consumer connection, and support the growth of Jack Beans Sauce in an increasingly competitive marketplace.